Incorporation of Product Carbon Footprint in the Sourcing Process of Electronic Components. A Case Study of a Global Automotive Company and a First-tier Supplier - Karlsson, Elisa; Sheik, Sally (My University, 2022)
Today, society is well aware of the global warming of our planet and the need to protect the environment. This puts pressure on companies worldwide, and the automotive industry is an example of an industry in need of change to meet the environmental pressure. Since vehicles are currently going through a digital transformation, they are built with a large number of electronic components. Those components have a significant impact on the global warming potential and thus actions need to be taken to reduce the negative impact. Since the procurement function handles the material flow into a company, research has shown that the department significantly contributes to the organisation’s environmental performance. Therefore, there is a need for incorporating more green sourcing practices. One type of green sourcing practice is to let suppliers conduct product carbon footprint (PCF) on the components they sell. This method generates a CO2 impact number in kilograms for the component, hence it enables the buying company to choose the component with the lowest CO2 number. Thus, this thesis aims at conducting a PCF on a specific electronic control unit (ECU). It will further investigate how PCF can be incorporated in the sourcing processes of electronics. To fulfil the aim of the study, a single-case study with a global automotive company and a first-tier supplier was performed. In the study, a PCF was conducted on the ECU by using material data from the supplier and general environmental data in a software program. Furthermore, nine interviews were held with 13 representatives from the focal automotive company and the first-tier supplier. A theoretical frame of reference was also established to discuss the empirical findings from the interviews and the gained experience from conducting the PCF. In the findings, eight drivers for incorporating PCF in sourcings’ were identified, i.e., it can improve organisations’ environmental performance, reduce organisational costs, help companies avoid violations of environmental regulatory laws, create a competitive advantage, improve organisational performance, meet customer requirements, protect firms images and increase collaboration with suppliers. Additionally, seven barriers were identified, i.e., internal costs, alignment of goals, complexity of supply chain, low maturity of using green sourcing practices, lack of transparency from suppliers and supplier-related costs. Furthermore, five capabilities were identified which are important in a successful incorporation. These are: the liaison between procurement and other business units, detailed procurement procedures, partnership approach with suppliers, digital systems and technical skills of procurement and advanced understanding of environmental issues in supply. Lastly, the conducted PCF on the ECU showed that the component emits 14,8 kilograms of CO2 equivalents from raw material extraction until its finalised and exits the first-tier supplier’s gate.
Keywords: Green Sourcing, Product Carbon Footprint, Sustainability and Electronics.